Giving justice to listening: exploring the impact of a novel dialogical approach to mental wellbeing on healthcare staff - Nsiah, Isaac; Junghans, Cornelia; Taddese, Henock B.; Dentschuk, Anna; de Mesquita, Amanda Bueno; Ball, Matthew (Frontiers in Psychology, 2025)
IntroductionA recent survey among health care workers in the United Kingdom revealed that over 75% experienced a mental health problem in the past year, with 42% reporting chronic stress. Poor mental wellbeing adversely affects patient outcomes and places a financial burden on the NHS. To address this issue, a novel dialogical approach called “Just Listening” (JL), originally used in community settings in Australia, has been introduced to train frontline workers in the United Kingdom. JL aims to maintain human-to-human connection and offers intentional listening. Evidence shows it to be effective in improving mental wellbeing of members in the community. It is unknown how effective this approach is in improving mental wellbeing when applied to training healthcare staff. This study aims to explore perceptions of JL training amongst a variety of health professionals and how JL can be utilised to improve mental health and wellbeing in a health care context.MethodsWe employed qualitative methodology, gathering data through semi-structured interviews with healthcare workers who had undergone JL training in Westminster. We analysed 17 semi-structured interviews with a broad range of staff who had undergone training several months prior. We used self-determination theory and transformational learning theory as guiding conceptual frameworks. In addition, we applied thematic analysis to post-course feedback gathered from participants to explore if views of the training differ between the time of the training (post course feedback) and several months later when the interviews were carried out. Analysis was conducted using Nvivo 14.ResultsThe study revealed five key themes: the power of listening, shifting perspectives, empowerment and professional development, enhanced work relationships and implementation. Themes across the immediate post-training feedback and structured interviews overlapped. Participants reported that JL training improved team and client relationships as well as their personal lives, leading to improved mental wellbeing. However, system constraints were identified as a challenge, emphasizing the need for support from senior management and policymakers to further enable its use.DiscussionThis was the first study to evaluate JL in the United Kingdom and in a healthcare setting. Our findings show that there was an overwhelming impression of positive impact of the training on the professional and personal lives of healthcare staff. This study contributes to the growing body of knowledge on mental health interventions for healthcare professionals, providing evidence that can inform future practices and policies. JL presents a viable model to improve staff wellbeing. Our findings reinforce growing calls for a culture shift towards human connection.